Tractates Šeqalim, Sukkah, Roš Haššanah, and Yom Tov (Besah) - Guggenheimer, Heinrich W. (Studia Judaica, 2014)
This volume of the Jerusalem Talmud publishes four tractates of the Second Order, Šeqalim, Sukkah, Roš Haššanah, and Yom Tov. These tractates deal with financial issues concerning the Temple service, with the festival of Tabernacles, the observations at New Year, as well as with holiday observation in general. The tractates are vocalized by the rules of Rabbinic Hebrew accompanied by an English translation and an extensive commentary.